2019
DOI: 10.1111/csp2.107
|View full text |Cite
|
Sign up to set email alerts
|

What constitutes a useful measure of protected area effectiveness? A case study of management inputs and protected area impacts in Madagascar

Abstract: Protected areas are one of the key tools for conserving biodiversity and recent studies have highlighted the positive impact they can have in avoiding habitat conversion. However, the relationship to management actions on the ground is far less studied and we currently do not know which management actions are the most crucial for success. To investigate this, we studied the effectiveness of the protected area network of Madagascar. We estimated the impact of individual protected areas in avoiding deforestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Potential limitations. We note that commonly used approaches to assess PA effectiveness have their caveats 46 . For instance, a lack of difference between densities in PA and non-PA sites does not necessarily indicate whether PAs are being ineffective, unless accounting for pressures separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential limitations. We note that commonly used approaches to assess PA effectiveness have their caveats 46 . For instance, a lack of difference between densities in PA and non-PA sites does not necessarily indicate whether PAs are being ineffective, unless accounting for pressures separately.…”
Section: Resultsmentioning
confidence: 99%
“…This was aimed at questioning whether increasingly used approaches to assess effectiveness in mitigating deforestation should also be used to evaluate wildlife trends. Although caveats in matching methods have also been denoted in the latter applications 46 , their use is still preferred. When it comes to wildlife trends, we noted that data of the required extent will rarely be available.…”
Section: Resultsmentioning
confidence: 99%
“…Inputs dominate assessment of CA management effectiveness (PAME), a prominent activity globally [8,11]. Inputs can be marginally related to biodiversity outcomes [12,13], but the relationship between PAME and impacts of terrestrial CAs has been elusive [14][15][16] (but see [17]), although a connection has been demonstrated for inshore marine CAs [18].…”
Section: Measuring Means or Ends?mentioning
confidence: 99%
“…With the CBD post-2020 framework being decided in 2021, there is still little evidence for Madagascar on the effectiveness of the protected area network for protecting its biodiversity heritage. While deforestation continues unabated (e.g., [15,18]), studies conducted by Eklund et al [19] or Yesuf et al [20] concluded that PAs in Madagascar could slow down deforestation. While Madagascar now has a network of protected areas across its main forests, only a few sites receive the bulk of attention from research, tourism, and NGOs [15,16,21].…”
Section: Introductionmentioning
confidence: 99%